Persistensi dan Pematahan Dormansi Benih pada Beberapa Varietas Padi Gogo - Satriyas Ilyas; Wan Tin Diarni (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Persistence and Breaking Seed Dormancy of Land Rice CultivarsABSTRACT. Previous studies have been done to break seed dormancy in rice (Oryza sativa L.). However, since the behavior of seed dormancy are different for different varieties, there is a need to find effective methods for breaking dormancy in four most important cultivars of low land rice. Low land rice seeds were harvested at 95 days after planting (cv. Kalimutu and cv. Gajah Mungkur), 105 dap (cv. Way Rarem) or 115 dap (cv. Jatiluhur), and dried to 13% moisture content. The seeds were stored in an envelope paper at ambient temperature and relative humidity (28-310C, RH 81-89%) for up to 9 weeks with 1 week interval. Persistency of seed dormancy in each cultivar was determined based on the time needed to reach a minimum of 85% germination capacity. Various methods of breaking dormancy were applied: untreated control, soaking in water for 24 h, soaking in water for 48 h, soaking in 1% KN03 for 24 h, soaking in 1% KN03 for 48 h, soaking in 120 ppm GA3 for 24 h, soaking in 120 ppm GA3 for 48 h, heating 500C for 72 h, heating 500C for 48 h + heating in water for 24 h, heating 500C for 48 h + heating in water for 48 h, heating 500C for 48 h + heating in 1% KN03 for 24 h, heating 500C for 48 h + heating in 1% KN03 for 24 h, soaking in water for 24 h + in damp cloth for 24 h, mantriconditioning using sawdust and mantriconditioning using rice hull ash. Soon after the treatment the seeds were germinated, and seed viability and vigor were observed. Results of experiment showed the viability and vigor of low land rice seeds were increased after storage. Persistence of seed dormancy was different in each cultivar i.e. 3 weeks in Kalimutu (germination capacity 90%), 4 weeks in Way Rarem (87%), 6 weeks in Gajah Mungkur (92%), and 9 weeks in Jatiluhur (85%). Soaking the seeds in 1% KN03 for 48 h was the most effective method for breaking dormancy of Kalimutu, Gajah Mungkur and Way Rarem at harvest (0 weeks). Heating the seeds in a 500C oven for 48 h followed by soaking in water 24 h was the only effective method to break dormancy in cv. Jatiluhur at 2 weeks after harvest, while the time of harvest none of the method was effective.